1993
DOI: 10.1056/nejm199306103282302
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Impaired Endothelium-Dependent Coronary Vasodilatation in Patients with Angina Pectoris and Normal Coronary Angiograms

Abstract: These findings suggest that endothelium-dependent dilatation of the resistance coronary arteries is defective in patients with anginal chest pain and normal coronary arteries, which may contribute to the altered regulation of myocardial perfusion in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
199
0
18

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(225 citation statements)
references
References 32 publications
8
199
0
18
Order By: Relevance
“…Many studies have demonstrated a prominent role of vascular health in normal systemic physiology [1][2][3] . However, age 4 , cardiovascular risk factors 5 , and cardiovascular disease 6 adversely affect vascular health.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated a prominent role of vascular health in normal systemic physiology [1][2][3] . However, age 4 , cardiovascular risk factors 5 , and cardiovascular disease 6 adversely affect vascular health.…”
Section: Introductionmentioning
confidence: 99%
“…6) Although ED has been associated with the presence of atherosclerosis, impaired endothelial-dependent NO bioactivity has also been shown in patients with atherosclerosis risk factors without overt vascular disease. [7][8][9][10][11] It has also been shown that NO is essential for flow-mediated dilatation of large human arteries in vivo. 12) Therefore, the purpose of this study was to measure plasma NO levels in patients with SCF and to compare them with normal coronary flow (NCF).…”
mentioning
confidence: 99%
“…There are no documented values for increase in coronary flow velocity after NTG administration in healthy children, but our results are comparable to values obtained in healthy adults. 24,25 …”
Section: Discussionmentioning
confidence: 99%